2021
DOI: 10.1088/1361-6579/ac2131
|View full text |Cite
|
Sign up to set email alerts
|

Motion robust ICG measurements using a two-step spectrum denoising method

Abstract: Objective. Impedance cardiography (ICG) is a noninvasive and continuous method for evaluating stroke volume and cardiac output. However, the ICG measurement is easily interfered due to respiration and body movements. Taking into consideration about the spectral correlations between the simultaneously collected ICG, electrocardiogram (ECG), and acceleration signals, this paper introduces a two-step spectrum denoising method to remove motion artifacts of ICG measurements in both resting and exercising scenarios.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…The critical characteristic points in ICG are also clearly observable, including B, C, X, and O that represent the opening of the aortic valve, maximum ejection velocity, closing of the aortic valve, and opening of the mitral valve, respectively ( 45 ). The pre-ejection period (i.e., time elapse between the Q point in ECG and B point in ICG) represents the period of left ventricular contraction with cardiac valves closed, indicative of heart sympathetic innervation ( 47 ). Because of the porous EGaIn composite’s large stretchability, ultrasoftness, and stable conductance over strain, the obtained skin-interfaced electrodes and interconnection cables can enable steady biosignal recording with high signal-to-noise ratios (SNRs) under dynamic deformations ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The critical characteristic points in ICG are also clearly observable, including B, C, X, and O that represent the opening of the aortic valve, maximum ejection velocity, closing of the aortic valve, and opening of the mitral valve, respectively ( 45 ). The pre-ejection period (i.e., time elapse between the Q point in ECG and B point in ICG) represents the period of left ventricular contraction with cardiac valves closed, indicative of heart sympathetic innervation ( 47 ). Because of the porous EGaIn composite’s large stretchability, ultrasoftness, and stable conductance over strain, the obtained skin-interfaced electrodes and interconnection cables can enable steady biosignal recording with high signal-to-noise ratios (SNRs) under dynamic deformations ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Monitoring heart electrical activity via ECG outside clinical settings plays an indispensable role in diagnosis of heart diseases (43,44). Concurrent measurement of cardiac mechanical function by ICG can reveal critical information that complements those associated with ECG (45)(46)(47). The wearable system based on porous EGaIn composites can perform high-fidelity ECG and ICG recording even during motions.…”
Section: Imperceptible Artifact-free Skin-interfaced Bioelectronicsmentioning
confidence: 99%
“…ICG is a tricarbocyanine dye that was developed using NIR technology in 1955 and permitted by the Food and Drug Administration (FDA) immediately for clinical use . ICG is widely employed in cancer diagnosis and other fields including angiography, cardiac output assessment, hepatic function evaluation, endoscopic endonasal surgery, and photodynamics and photothermal therapy. In addition to the above applications, the ICG application for SLN is also promising. ICG-guided SLN biopsy reduces surgical time and improves lymph node detection, remaining an intact surgical anatomy .…”
Section: Fluorescent Probes In Lymph Node Mapping For Tumor Micrometa...mentioning
confidence: 99%
“…In [ 50 , 51 , 52 ], it was shown that EMD can be extremely useful in the identification of cardiovascular diseases. It also facilitates the detection of characteristic points of this signal [ 53 ] and allows for effectively suppressing noise without losing significant features in the acquired recordings [ 54 , 55 ]. Here, we propose a novel, EMD-based method that allows for the accurate detection of fiducial points in the ICG signal.…”
Section: Introductionmentioning
confidence: 99%